HUBUNGAN BEBAN KERJA FISIK DAN POSISI DUDUK TERHADAP KELUHAN LOW BACK PAIN PADA KURIR BERSEPEDA MOTOR PT SPY CIRACAS TAHUN 2023 - Annisa Mutiara Sari, (2024)
Motorcycle couriers have physical demands, such as manual lifting, an unstable working environment, and an awkward riding position which could inadvertently trigger complaints of low back pain. This study aimed to determine the correlation between physical workload and sitting position with low back pain complaints among motorcycle couriers employed at PT SPY Ciracas. This study used a crosssectional design with a research sample of 95 respondents obtained through a simple random sampling technique. The research instruments used the Modified Oswestry Disability Index (ODI), Rapid Entire Body Assessment (REBA) observation sheet, International Physical Activity Questionnaire short-form (IPAQ-sf), and Brinkman Index. A pulse oximeter was utilized to measure the physical workload. The study used chi-square and binary logistic regression test analysis. The multivariate analysis showed a significant correlation between physical workload (p = 0,000;POR = 34,28; 95% CI: 7,73 - 152,12) and light physical activity (p = 0,001; POR = 31,28; 95% CI: 4,44 - 220,45) towards complaints of low back pain. The physical workload is the main factor contributing to complaints of low back pain. The company can enhance employees' understanding and abilities regarding the importance of ergonomic aspects in the workplace through regular medical checkups, group sports activities, and educational training.